Composição, dinâmica e diversidade da comunidade de aves em uma paisagem heterogênea da Serra do Amolar – Pantanal-Brasil - Reny da Silva Rodrigues (2021)
Despite remarkable significance of Pantanal for the bird conservation, this large wetland presents areas where the birds are poorly known, such as the Serra do Amolar. This wetland is a priority area for conservation, but shows a high Wallacean deficit. Thus, we carried out a bird survey to verify the diversity and composition of birds in the five habitats of Serra do Amolar (February 2020 and 2021). We adopted both the point count (80 hours) and transect (40 hours) methods. We recorded 290 species, 37 of which were new records for the Serra do Amolar, nine new species are registered in MS and we documented the first records of Crypturellus strigulosus, Nothura boraquira and Hemithraupis flavicollis for the Pantanal. These new records show the evident Wallacean deficit in the Serra do Amolar. PcoA showed difference in bird composition (r2 = 0.1642, p = 0.001) and species composition differed among environments (r2 = 0.4895, p = 0.001). Beta diversity varies from Bw = 0.51 [between Bosque Chiquitano (BC) and Baia (BA)] to Bw = 0.30 [between Semideciduous Forest (FS) and Campo Limpo (CL)]. Floresta Ripária / Rio (RR) (172 spp., 33% abundance) and BA (166, 25%) present higher beta diversity, higher percentages of carnivores and the UPGMA (axis 1) separates them from other environments in the composition of avifauna. In axis 2, FS and BC are more similar to each other than to CL. Frugivores present the higher percentage in BC and lower in RR. All of these similar parameters between forest and terrestrial environments (BC, FS and CL), as well as between aquatic environments (RR and BA), indicate high habitat selection and the high gama diversity of birds shows the importance of maintaining this environmental heterogeneity. These bird composition data in preserved habitats will serve as a parameter to verify the disturbance levels in altered Pantanal habitats.